A Study on Knowledge Towards Brain Death among Residents in Indonesia - Fauzi, Asra Al; Waloejo, Christrijogo Sumartono; Machin, Abdulloh; Shodiq, Muhammad Ja'far (Folia Medica Indonesiana, 2020)
This research was conducted to evaluate the knowledge and diagnosis of brain death among resident in Indonesia. This study used an observational analytic study with a cross-sectional study design using a questionnaire. The research subjects consisted of 132 level 2 (after 2 years of residency) and level 3 (after 4 years of residency) residents, the total sampling for which was taken from the departments of Neurosurgery, Anesthesiology, and Neurology at Dr. Soetomo Academic Medical Center Hospital, Surabaya, Indonesia. Data were taken from November 2018 to January 2019. A total of 132 residents of Neurosurgery, Neurology, and Anesthesiology participated in this study. From the series of studies, residents' knowledge of the concept of brain death was in the sufficient category (41.7%), residents' knowledge of the technical diagnosis of brain death was in the good category (40.2%), residents' knowledge of brain death examination was in the less category (43.2%), and finally, it was found that the resident's knowledge of brain death was in a good category (35.6%). There were also significant differences in knowledge of brain death between Neurosurgery, Neurology, and Anesthesiologist Resident (P <0.001) and knowledge of brain death between level 2 and level 3 residents (P=0.032). In general, the Indonesian resident doctors' knowledge of brain death is adequate, but knowledge of the clinical examination of brain death is still lacking. Further research must be carried out to promote knowledge of brain death in residents as well as professional doctors/specialists, so that the number of organ transplants, especially in Indonesia, will increase.